When the Use of Positive Language Backfires: The Joint Effect of Tone, Readability, and Investor Sophistication on Earnings Judgments - TAN, HUN‐TONG; YING WANG, ELAINE; ZHOU, BO (Journal of Accounting Research, 2014)
ABSTRACT Recent studies document that market participants react positively to the positive language sentiment or tone embedded in financial disclosures, and that investors’ reactions to negative news are more muted with poor disclosure readability. However, while language sentiment and readability co‐occur in practice, their joint effects remain largely unexplored. In an experiment with MBA students as participants, we investigate how the effect of language sentiment varies with readability and investor sophistication level. We find that language sentiment influences investors’ judgments when readability is low, but not when readability is high. Specifically, when readability is low, disclosures couched in positive language lead to higher earnings judgments for less sophisticated investors, but lower earnings judgments for more sophisticated investors. These findings show that the main effects of readability and language sentiment documented in prior studies have boundary effects, and may reverse when both variables are jointly considered along with investor sophistication.